Exploratory study of sugar and C6 compounds in single berries of grapevine (Vitis vinifera L.) cv. Cabernet Sauvignon throughout ripening. (25th February 2021) - Previtali, P.; Dokoozlian, N.; Capone, D.L.; Wilkinson, K.L.; Ford, C.M.
Abstract: Background and Aims: This study explored changes in the profile of selected aroma compounds in individual berries during development to establish whether a correlation exists between aroma compounds and sugar. Previous studies have assessed changes in the aroma compounds of ripening grapes using multiple berries randomly pooled together or sorted according to their diameter, density or colour. These data, while of value from a winemaking perspective, may prevent a fine interpretation of the compositional changes within individual berries characterised by asynchronous development. Methods and Results: Individual berries of Vitis vinifera cv. Cabernet Sauvignon at different stages of development were sampled from veraison to harvest. Sugar concentration and mass of individual berries were measured, and C6 compounds analysed. The content of C6 compounds per berry was strongly correlated to the stage of development, while changes between stages were compound specific. Berries of similar TSS shared comparable composition of C6 compounds, with little influence of the sampling date. Conclusions: Investigation of the composition of individual berries during ripening showed a strong dependency between the stage of development and the composition of sugar and C6 compounds. Significance of the Study: Compositional changes of metabolites occurring in individual grape berries throughout ripening were identified. This study provides a starting point for a detailed study of the sugar/flavour nexus that may lead to an improved understanding of how to produce grapes with less sugar and more aroma, to overcome challenges associated with climate change.